If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -30x = (-27) + -63 -30x = -27 + -63 Combine like terms: -27 + -63 = -90 -30x = -90 Solving -30x = -90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-30'. x = 3 Simplifying x = 3
| 42-14=4(x-2) | | -2/5x-5/3-9/5 | | 395=200+0.25x | | p^2+260p-500=0 | | 18w=36 | | 3(2x-5)=2(4-x) | | (x+6)(5x-7)= | | 3+5x=6x-2 | | -9*7=6 | | Y(t)=t^2+4t+4 | | f(x)=x-10/6 | | 8-8=10x+4 | | 3j=37 | | 7p+6.9=15.6+6p | | 5x/(2*5)=10 | | x^4+20x^2-192=0 | | -3y+7=-7y | | 121/11=x | | 2e^15x=15 | | m=-5,(7,9) | | [8n-10]=46 | | 3x-y-x-y=-2x-y | | n+(n*0.045)=1500 | | -8s=8 | | n+(n*0.45)=1500 | | (2y+5)(3y-4)= | | 5.9+1.8x=2.8x | | -x-4y=-6 | | 48x+2x+20=180 | | 3(2x+3)-5(c-1)=9 | | 10/(2x-3)=7/(3x) | | 0=-16(t)(t)+64t+80 |